CALCIUM ABSORPTION KINETIC ON INDONESIAN RICE - Chatarina Wariyah; Mary Astuti; Supriyadi Supriyadi; Chairil Anwar (Indonesian Journal of Chemistry, 2008)
Calcium absorption kinetic from three varieties rice i.e. low-, medium-, and high amylose content were evaluated. Three calcium salt (calcium acetate, -lactate and - gluconate) were used as a fortifican. Each rice was soaked at the calcium salts at soaking temperatures of 80, 90 and 100 oC, for 30 min and the calcium content was analyzed periodically. Reaction rate constant was determined from slope of curve of the relation of soaking time and absorbed calcium. The activation energy was determined by Arrhenius equation. The research showed that rice calcium absorption follows the first-order kinetic and absorption rate tends to decrease with increasing temperature. Calcium absorptions were affected by calcium salt solubility. Calcium acetate was absorbed easier than calcium lactate and calcium lactate was absorbed easier than calcium gluconate, but the absorption rate constant of calcium acetate was lower than that of calcium lactate, and calcium lactate was lower than calcium gluconate. Based on amylose content of rice, the higher the amylose content, the lower calcium absorption rate. The activation anergy of the high amylose rice was higher than that of low amylose content.